Cytomegalovirus Infection and Relative Risk of Cardiovascular Disease (Ischemic Heart Disease, Stroke, and Cardiovascular Death): A Meta‐Analysis of Prospective Studies Up to 2016. Issue 7 (July 2017) - Wang, Haoran; Peng, Geng; Bai, Jing; He, Bing; Huang, Kecheng; Hu, Xinrong; Liu, Dongliang
Abstract : Background: Several studies have suggested that cytomegalovirus infection is likely associated with an increased relative risk of cardiovascular disease (CVD); however, the results are inconsistent. We aimed to provide a systematic review and meta‐analysis of community‐based prospective studies assessing the association between cytomegalovirus infection and relative risk of CVD. Methods and Results: We searched Medline and EMBASE to retrieve prospective studies that reported risk estimates of the association between cytomegalovirus infection and relative risk of CVD. The search yielded 10 articles including a total of 34 564 participants and 4789 CVD patients. Overall, exposure to cytomegalovirus infection was associated with a 22% (relative risk: 1.22, 95% CI: 1.07–1.38, P =0.002) increased relative risk of future CVD. We estimated that 13.4% of CVD incidence could be attributable to cytomegalovirus infection. Conclusions: In conclusion, cytomegalovirus infection is associated with a significantly increased relative risk of CVD.